Karakteristik Fisik Beras Analog dari Jagung Berkadar Amilosa Sedang dengan Menggunakan Ulir Ekstruder Kecepatan Menengah - Faleh Setia Budi; Purwiyatno Hariyadi; Slamet Budijanto; Imam Perdana Putra (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2024)
Indonesia has the highest rice consumption rate in the world, averaging 130 kg per capita per year. Despite government efforts to reduce this through food diversification programs, there has been little success. One approach to reducing rice consumption is to process non-rice ingredients into rice analogues that have similar characteristics to traditional rice. The amylose content of the ingredients plays a significant role in determining the physical properties of these rice analogues. Additionally, the screw speed of the extruder used in the production process also influences these physical characteristics. This study aimed to explore the impact of extruder screw speed and material amylose content on the physical properties of rice analogues. Local corn flour was mixed with high-amylose corn starch to create mixtures with amylose contents of 16.99, 19.35, 21.72% and 24.08%. The tested screw speeds were 100, 125, and 150 rpm. The evaluated physical characteristics included the hardness of the rice analogues, bulk density, cooked rice hardness, gumminess, and sensory properties of the cooked rice. The results showed that as amylose levels increased, the hardness of the rice analogues, cooked rice hardness, and gumminess also increased. Similarly, increasing the screw speed of the extruder led to higher cooked rice hardness, gumminess, and rice analogue hardness, but it decreased bulk density. The optimal extruder operating conditions were found to be an amylose content of 21.72% and a screw speed of 100 rpm, producing rice analogues with a hardness of 3610 gf, a bulk density of 0.63 g/mL, a cooked rice hardness of 3200 gf, and gumminess of 1200 gf.